Parent involvement : collaboration is the key for every child's success - Wages, Michele, 1965- (Rowman & Littlefield, 2016)
In today's economy, where getting a good education has never been more important and school resources are stretched beyond points that most of us can remember, it is imperative that parents be fully engaged in their child's education, both at home and at school. Parents play an integral role regardless of their ability to assist their children in specific subject areas or skills by encouraging their student to promote competence, control, and positive attitudes towards academics. Whether you are an educator or a parent, this book discusses barriers and methods to overcome them in order to buil.